Water reclamation and nitrogen extraction from municipal solid waste landfill leachate. Issue 60 (25th December 2016) - Nghiem, Long D.; Hai, Faisal I.; Listowski, Andrzej
Abstract: This study aims to explore several innovative technologies including electrocoagulation, nanofiltration (NF), membrane distillation (MD), and ion exchange resin for clean water extraction and resource recovery from landfill leachate. Our results demonstrate the technical feasibility of water reuse and ammonia recovery from landfill leachate. Electrocoagulation was effective as a pretreatment step for the NF process and could remove most suspended solids and some organic matter. The results show that the combination of NF and MD can produce high-quality water from landfill leachate suitable for reuse applications with respect to heavy metals (with the exception of arsenic) and pharmaceutically active compounds (PhACs). Heavy metal concentrations in the NF permeate were below the values specified by the Australian Guidelines for Water Recycling. PhAC removals by the NF process were in the range of 67–97%. Heavy metals and PhACs were not detectable in the MD distillate. The recovery of ammonia from NF permeate by a strong acid ion exchange resin was also demonstrated.